ANTESEDEN CUSTOMER LOYALTY PADA LOW COST CARRIER AIRLINE - Marcella Harlan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2015)
The background of this research was Customer loyalty as a competitive advantage in serviceindustry.The design of this research applies a survey toward unit of analysis on Low Cost CarrierAirline to interview the passanger for testing hypothesis. Meanwhile the required data consist offive variables; Recovery Satisfaction, Corporate Social Responsibility, Customer Trust, CustomerLoyalty. The aggregate numbers of customer being respondent of the study are 200. Data analysisused in this research was consists of Path Method by AMOS 22.0 as software. The result of thisresearch conclude that variable of Recovery Satisfaction, Corporate Social Responsibility haspositive effect to Customer Trust; Recovery Satisfaction, Corporate Social Responsibility has positiveeffect to Customer Loyalty; and Customer Trust has positive effect to Customer Loyalty.Keywords: Service Recovery Satisfaction, Corporate Social Responsibility, Customer Trust,Customer Loyalty, Low Cost Carrier Airline.